2017
DOI: 10.1177/2325967117707477
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Head-to-Head Comparison of 2 Sutures and the Giftbox Versus Bunnell Techniques for Midsubstance Achilles Tendon Ruptures

Abstract: Background: Acute midsubstance Achilles tendon ruptures are a common orthopaedic problem for which the optimal repair technique and suture type remain controversial. Head-to-head comparisons of current fixation constructs are needed to establish which stitch/suture combination is most biomechanically favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
(59 reference statements)
0
22
1
Order By: Relevance
“…Therefore, this study could not determine whether early functional rehabilitation could be performed. Van Dyke [10] conducted a biomechanical test for the Giftbox suture, and no clinical failure was observed from 20 to 100 N over 10 0 0 cycles. The clinical load to failure was 373 ± 110 N, and the catastrophic failure was 379 ± 103 N for the Giftbox technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study could not determine whether early functional rehabilitation could be performed. Van Dyke [10] conducted a biomechanical test for the Giftbox suture, and no clinical failure was observed from 20 to 100 N over 10 0 0 cycles. The clinical load to failure was 373 ± 110 N, and the catastrophic failure was 379 ± 103 N for the Giftbox technique.…”
Section: Discussionmentioning
confidence: 99%
“…The site from which the stitch exits after passing through the loops was located at the corner of the last locking loop. concentrated stress at the crossing site may easily lead to failure of the knot or destroy the transverse limb [10] .…”
mentioning
confidence: 99%
“…Previous biomechanical studies have shown that the giftbox core suture technique has less tendon gapping and greater elongation to failure strength. 27,55 Lee and colleagues reported improved Achilles tendon strength with the addition of an epitendinous cross-stitch weave augmentation. 29…”
Section: Discussionmentioning
confidence: 99%
“…5 Using simulated early rehabilitation biomechanical testing, Van Dyke et al showed that Giftbox-modified Krackow Achilles repair technique with FiberWire suture was stronger and more resistant to gap formation at the repair site than combinations that incorporated the Bunnell stitch or Ultrabraid suture. 2 Hong et al found no difference in cyclic load and load to failure between needleless knot techniques and Krackow configurations. 6 Ostrander et al found no difference to elongation in cyclic load between modified Krackow and modified locking Speedwhip stitch.…”
Section: See Related Article On Page 663mentioning
confidence: 98%
“…Today, Krackow stitches continue to be widely employed for a variety of large and small tendon repairs and reconstructions including Achilles, quadriceps, and patella tendon repair among others. [1][2][3] Surgeons continue to seek ways to improve the biomechanical strength of the construct while maintaining tendon vascularity and tissue morphology. .…”
Section: See Related Article On Page 663mentioning
confidence: 99%